Systematic Literature Review: Sistem Informasi Rekam Medis Berbasis Web - An Nisa Dira; Ines Heidiani Ikasari (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Web-based medical record information systems have become an important research area to increase the efficiency and accuracy of medical data management. Web-based SIMR has various potential benefits. In this journal, a literature review is presented which aims to describe the development and benefits of web-based SIMR implementation. The results of the literature review show that a web-based medical record information system can provide several significant benefits. Some of its key benefits include better data accessibility, easier sharing of information between healthcare facilities, increased administrative efficiency, and improved coordination of patient care. In addition, web-based SIMR can also facilitate the exchange of medical information between various health systems and facilities. The Literature Review also identified several challenges associated with the development and implementation of a web-based medical record information system. These challenges cover issues of privacy and data security, technology infrastructure, data quality, and integrity, as well as regulation and compliance.